2018
DOI: 10.3390/scipharm86020012
|View full text |Cite
|
Sign up to set email alerts
|

N-Aryl-7-hydroxy-5-oxo-2,3-dihydro-1H,5H-pyrido-[3,2,1-ij]quinoline-6-carboxamides. The Synthesis and Effects on Urinary Output

Abstract: Continuing a targeted search for new leading structures with diuretic action among tricyclic derivatives of hydroxyquinolines, which are of interest as potential inhibitors of aldosterone synthase, the synthesis of a series of the corresponding pyrido[3,2,1-ij]quinoline-6-carboxanilides was carried out by amidation of ethyl-7-hydroxy-5-oxo-2,3-dihydro-1H,5H-pyrido[3,2,1-ij]quinoline-6-carboxylate with aniline, aminophenols and O-alkylsubstituted analogs with high yields and purity. The optimal conditions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In addition, the analysis of the fragmentation ions that are formed during the primary fragmentation of molecular ions also provides the analytically important information about the components of the molecule under study (Scheme 2). It has been shown in the example of benzylamide 2a, which is typical for the whole group studied, that this process proceeds by the ketene type that is common for 4-hydroxy-2-oxo-1,2-dihydroquinoline-3-carboxamides and their tricyclic analogs [25,26], namely after breaking of the acyclic amide bond two characteristic fragments-the ion of tricyclic ketene 8 with m/z 227 and the ion of arylalkylamine 9, which is specific for each sample, are formed. provides the analytically important information about the components of the molecule under study (Scheme 2).…”
Section: Chemistrymentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, the analysis of the fragmentation ions that are formed during the primary fragmentation of molecular ions also provides the analytically important information about the components of the molecule under study (Scheme 2). It has been shown in the example of benzylamide 2a, which is typical for the whole group studied, that this process proceeds by the ketene type that is common for 4-hydroxy-2-oxo-1,2-dihydroquinoline-3-carboxamides and their tricyclic analogs [25,26], namely after breaking of the acyclic amide bond two characteristic fragments-the ion of tricyclic ketene 8 with m/z 227 and the ion of arylalkylamine 9, which is specific for each sample, are formed. provides the analytically important information about the components of the molecule under study (Scheme 2).…”
Section: Chemistrymentioning
confidence: 94%
“…The transition to pyridoquinolines XI did not meet the expectations. Based on the tests conducted, it can be argued that, as a rule, the diuretic activity is somewhat reduced as a result of such a transformation, and the structure of the amide fragments affects the biological properties in the same way as in the pyroloquinolines VIII group [24,25]. At the same time, it has been found that bromination of the pyridoquinoline nucleus in position 9 (amides XII) leads to a significant increase in diuresis and, in principle, opens a new direction of "me-too" optimization of tricyclic 4-hydroxyquinoline-2-one diuretics [26].…”
Section: Sci Pharm 2018 X X For Peer Review 4 Of 20mentioning
confidence: 99%
“…Two 6-hydroxy-2-methyl-4-oxo-2,4-dihydro-1Hpyrrolo[3,2,1-ij]quinoline-5-carboxamides (Ia: R=2-COOH-C 6 H 4 ; Ib: R=CH 2 C 6 H 5 ) with the highest diuretic activity [20] were chosen as the ligands for docking study.…”
Section: Planning (Methodology) Of Researchmentioning
confidence: 99%
“…Having limited list of perspective structures, their laboratory synthesis would be greatly reduced in price. The proposed method [20,21] for synthesis of 6-hydroxy-2-methyl-4-oxo-2,4-dihydro-1Hpyrrolo[3,2,1-ij]quinoline-5-carboxamides (I) and 7hydroxy-5-oxo-2,3-dihydro-1H,5H-pyrido[3,2,1-ij]quinoline-6-carboxamides (II) opens up possibility to vary substituents on amide group for obtaining related compounds and completing the structure optimization of an identified lead compound in the future.…”
Section: Table 2 Statistical Characteristics Of Qsar Modelsmentioning
confidence: 99%
See 1 more Smart Citation